Leptochilus tridigitatus (Polypodiaceae), a new fern species from Guangdong, China - Wei, Hong-Jin; Qiu, Yong-Ling; Huang, Yi; Bin, Chen (Phytotaxa, 2024)
Leptochilus tridigitatus, a new microsoroid fern species of Polypodiaceae from southwestern Guangdong, China, is described and illustrated. The new species is morphologically highly variable and most similar to L. poilanei in dimorphic fronds and simple or trifid laminae, while its fertile fronds are most similar to some of those of L. digitatus. The new species can best be distinguished from L. digitatus but sometimes is confused with L. scandens due to its occasionally pinnatifid laminae with two pairs of lateral lobes. It might have been collected from South China and misidentified as L. digitatus or other Leptochilus species.